1998
DOI: 10.1016/s0375-9474(97)00634-9
|View full text |Cite
|
Sign up to set email alerts
|

What QCD sum rules tell about the rho meson

Abstract: Using a simple parametrization of Breit-Wigner type for the hadronic side of the QCD sum rule for ρ mesons in vacuum as well as in a nuclear medium we explore the range of values for the mass and the width of the ρ meson which are compatible with the operator product expansion.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
229
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(242 citation statements)
references
References 33 publications
12
229
1
Order By: Relevance
“…discussion above). We have checked that the use of a Borel sum rule in the way described in [16,35] leads to quantitatively similar results as compared to the ones presented here. We prefer to use the finite energy sum rules here since in this case the results can be presented in a closed analytic form.…”
Section: Qcd Sum Rulessupporting
confidence: 71%
“…discussion above). We have checked that the use of a Borel sum rule in the way described in [16,35] leads to quantitatively similar results as compared to the ones presented here. We prefer to use the finite energy sum rules here since in this case the results can be presented in a closed analytic form.…”
Section: Qcd Sum Rulessupporting
confidence: 71%
“…Even if one follows the arguments of points 1 to 4 it has been shown that besides a dropping mass also a broadened hadronic spectral distribution is compatible with the QCD sum rules [32,33]. One still seems to have at least a connection between chiral restoration -drop of two-and fourquark condensates -and in-medium changes, no matter whether it is a mass shift or a broadening or a more complicated in-medium modification [13,34].…”
Section: Introductionmentioning
confidence: 97%
“…where the Borel mass M has emerged from the OPE momentum scale Q (for further details we refer the interested reader to [33]). We consider a ρ meson at rest, therefore, the tensor structure of (5) reduces to a scalar Π = 1 3 Π µ µ .…”
Section: Introductionmentioning
confidence: 99%
“…As is well known for the ρ meson [15,16,17], the QCDSR cannot uniquely predict the in-medium properties of the spectral function, but it can provide constraints on model calculations. Weinberg sum rules (WSRs) relate chiral order parameters to energy moments of the difference between the vector and axialvector spectral functions [18],…”
Section: Qcd and Weinberg Sum Rulesmentioning
confidence: 99%